Al-Razi's contribution to the study of nexus between human mind and body - Abdulwaheed, Musa; Ismail, Ahmad Faris (IIUM Press, 2011)
The objective of this chapter is to discuss Razi's contribution to the development of traditional psychology, linking the human mind and body. It is of note that the significance of this chapter is appreciating efforts of Islamic thinkers and scientists like Razi and his valuable and outstanding contributions to the field of psychology. The method adopted in this research is based on library materials, internet sources and academic discussions. The theory and the research framework are limited to focusing mainly on reviewing the person of AI-Razi, nexus between the human mind and body and other similar Razi's outstanding contributions